(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Entrepreneurship development is a crucial issue in Indonesia due to limited employment opportunities, which contribute to high unemployment rates. This study aims to analyze the influence of family environment and self-efficacy on entrepreneurial interest, with entrepreneurial knowledge as a mediating variable. The study employed a quantitative approach with a causal design. Data were collected through structured questionnaires distributed to respondents, then analyzed using Structural Equation Modeling (SEM) because it involves direct and indirect relationships between variables. The analysis was conducted through the stages of instrument validity and reliability testing, measurement model testing, and structural model testing to examine the influence between variables. The results showed that family environment and self-efficacy have a positive and significant effect on entrepreneurial knowledge. Entrepreneurial knowledge also has a positive and significant effect on entrepreneurial interest. The family environment does not have a direct effect on entrepreneurial interest, while self-efficacy has a positive and significant effect. Furthermore, entrepreneurial knowledge has been shown to mediate the influence of family environment and self-efficacy on entrepreneurial interest.